2013
DOI: 10.4314/ijbcs.v6i5.24
|View full text |Cite
|
Sign up to set email alerts
|

Les plantes des galeries forestières à usage traditionnel par les tradipraticiens de santé et les chasseurs Dozo Sénoufo du Burkina Faso

Abstract: RESUME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 4 publications
6
15
0
3
Order By: Relevance
“…This result testifies TH knowledge about plants diversity of this area and their therapeutic virtues. Similar results were observed by previous studies [ 19 , 21 ] which showed that local populations of Burkina Faso were known to profit from the best part of biodiversity in traditional medicine. More than 77% of plants identified are ligneous.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result testifies TH knowledge about plants diversity of this area and their therapeutic virtues. Similar results were observed by previous studies [ 19 , 21 ] which showed that local populations of Burkina Faso were known to profit from the best part of biodiversity in traditional medicine. More than 77% of plants identified are ligneous.…”
Section: Discussionsupporting
confidence: 92%
“…This rate could be justified by the relative abundance of these species in the phytogeographical sector of this area, and their availability during all the year. These results were in the same order with those of Traoré’s group in the province of Comoé [ 36 ], Olivier’s group on “Dozo” traditional healers [ 21 ] and Zerbo’s group in western area [ 22 ], which indicates a prevalence of ligneous use in the pharmacopeia of this zone of Burkina Faso. S. longepedunculata , C. procera , K. senegalensis , A. sativum , D. oliveri , A. senegalensis were identified as the main species used and D. innoxia , Z. zanthoxyloïdes were only used by older TH.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…La forte citation exclusive de Pentadesma butyracea à Ziékorodougou qui borde la galerie de Farako illustre bien cette variation. Olivier et al (2012) ont indiqué que les usages alimentaires relèvent de la culture traditionnelle en pays Sénoufo.…”
Section: Les Espèces Ligneuses à Huile Pour L'alimentation Humaineunclassified
“…Localisation of Alchornea cordifolia in young forests is also widespread in riparian areas, usually marshy areas with dense thick formation where it is often identified as aquatic macrophytes (Dibong and Ndjouondo, 2014). It grows in rainforests along rivers and dominates (Olivier et al, 2012). It dominates in edaphic forests linked to hydromorphic soils and river forests.…”
mentioning
confidence: 99%